553 Assessment of jaw muscles and cervical spine muscles isometric force using a hand-held dynamometer in young adults (Balneo and PRM Research Journal, 2024)
Our study aims to investigate the jaw and cervical spine muscle isometric forces in healthy young adults. Fifty-four subjects (21.2 ± 4.82 years) met the inclusion criteria and agreed to participate in the study. Muscle forces were assessed with a hand-held dynamometer. A significant positive correlation was found between jaw opening forces and cervical flexors forces (r=0.62, p0.0001) and between lateral mandible deviation forces and cervical spine lateral flexion forces, both for right and left side (r=0.65, p